2014
DOI: 10.5194/acp-14-5905-2014
|View full text |Cite
|
Sign up to set email alerts
|

A climatology of the diurnal variations in stratospheric and mesospheric ozone over Bern, Switzerland

Abstract: Abstract. The ground-based radiometer GROMOS, stationed in Bern (47.95 • N, 7.44 • E), Switzerland, has a unique data set: it obtains ozone profiles from November 1994 to present with a time resolution of 30 min and equivalent quality during night-and daytime. Here, we derive a monthly climatology of the daily ozone cycle from 17 years of GRO-MOS observation. We present the diurnal ozone variation of the stratosphere and mesosphere. Characterizing the diurnal cycle of stratospheric ozone is important for corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 56 publications
6
49
2
Order By: Relevance
“…Thus, it seems that WACCM should be quite reliable with regard to information about the daily ozone cycle at any region. In addition, we find the daily ozone cycle of WACCM in good agreement with observations by a microwave radiometer at Bern, Switzerland (Studer et al, 2014), which operates as part of the frame of NDACC and with satellite-based observations of SMILES (Sakazaki et al, 2013) and TIMED or SABER (Huang et al, 2008). The surprising strong daily ozone cycle at high latitudes in polar summer is confirmed by observations of a ground-based microwave radiometer at Ny-Ålesund, Svalbard (Palm et al, 2013).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Thus, it seems that WACCM should be quite reliable with regard to information about the daily ozone cycle at any region. In addition, we find the daily ozone cycle of WACCM in good agreement with observations by a microwave radiometer at Bern, Switzerland (Studer et al, 2014), which operates as part of the frame of NDACC and with satellite-based observations of SMILES (Sakazaki et al, 2013) and TIMED or SABER (Huang et al, 2008). The surprising strong daily ozone cycle at high latitudes in polar summer is confirmed by observations of a ground-based microwave radiometer at Ny-Ålesund, Svalbard (Palm et al, 2013).…”
Section: Discussionsupporting
confidence: 67%
“…A similar increase of ozone during the afternoon was found in a climatology of the daily ozone cycle observed by the ground-based microwave radiometer GROMOS in Bern, Switzerland (Studer et al, 2014). Satellite-based observations from SMILES (Kikuchi et al, 2013), SABER and MLS showed a morning minimum and a late-afternoon maximum in the daily ozone cycle in the tropics and subtropics (Huang et al, 2008;Sakazaki et al, 2013).…”
Section: The Daily Ozone Cyclementioning
confidence: 52%
See 2 more Smart Citations
“…As a results, diurnal variations in ozone concentrations are observable in the upper stratosphere and lower mesosphere . Therefore, differences in ozone concentrations measured in the upper stratosphere-lower mesosphere could result from satellitebased instruments measuring ozone at a different solar zenith angles, i.e., different local time of the day (e.g., Pallister and Tuck, 1983;Schanz et al, 2014;Studer et al, 2014). With the current version of BSVertOzone, the potential differences in ozone measurements caused by the diurnal cycle are ignored as the effect on the monthly mean zonal mean ozone values is expected to be small.…”
Section: Discussionmentioning
confidence: 99%